THE POTENTIAL ROLE OF METFORMIN IN THE TREATMENT OF HASHIMOTO’S THYROIDITIS: REVIEW - Gabriela Kapłon; Weronika Perczyńska; Julia Szczotka; Gabriela Szpila; Remigiusz Flakus; Żaneta Kania; Aleksandra Sokół; Dominika Gieroba; Anna Kamieniak; Karolina Glajcar; Artur Tumiński; Marianna Chmiel (International Journal of Innovative Technologies in Social Science, 2025)
Background: Hashimoto’s thyroiditis is one of the most common autoimmune diseases, with a noticeable increase in incidence observed in recent years. Despite its high prevalence, current treatment options remain limited and primarily focus on managing the consequences rather than addressing the underlying causes of the condition. Metformin, although primarily prescribed for diabetes, has demonstrated promising anti-inflammatory and immunoregulatory properties in several autoimmune disease models. Aim: This review aims to evaluate the potential role of metformin in the management of Hashimoto’s thyroiditis, with a particular focus on its effects on immune regulation and thyroid function. Methods: An electronic literature search was performed using PubMed, Cochrane Library, ScienceDirect and Evidence‑Based Medicine Reviews. Search terms included ‘Metformin’, ‘Hashimoto disease’, ‘Thyroiditis’, ‘Thyroid’, ‘autoimmune disease’ as keywords. Only articles in English were considered. Conclusions: Preliminary data suggest that metformin, through its anti-inflammatory properties and modulation of AMPK/mTOR pathways, may influence immune responses in Hashimoto’s thyroiditis. Despite promising preclinical findings, further clinical trials involving human participants are required to evaluate its therapeutic efficacy and safety in this context.